Combination of Two Photosensitisers in Anticancer, Antimicrobial and Upconversion Photodynamic Therapy - Martina Mušković; Rafaela Pokrajac; Nela Malatesti (MDPI AG, 2023)
Photodynamic therapy (PDT) is a special form of phototherapy in which oxygen is needed, in addition to light and a drug called a photosensitiser (PS), to create cytotoxic species that can destroy cancer cells and various pathogens. PDT is often used in combination with other antitumor and antimicrobial therapies to sensitise cells to other agents, minimise the risk of resistance and improve overall outcomes. Furthermore, the aim of combining two photosensitising agents in PDT is to overcome the shortcomings of the monotherapeutic approach and the limitations of individual agents, as well as to achieve synergistic or additive effects, which allows the administration of PSs in lower concentrations, consequently reducing dark toxicity and preventing skin photosensitivity. The most common strategies in anticancer PDT use two PSs to combine the targeting of different organelles and cell-death mechanisms and, in addition to cancer cells, simultaneously target tumour vasculature and induce immune responses. The use of PDT with upconversion nanoparticles is a promising approach to the treatment of deep tissues and the goal of using two PSs is to improve drug loading and singlet oxygen production. In antimicrobial PDT, two PSs are often combined to generate various reactive oxygen species through both Type I and Type II processes.